El ilusionista Onofroff en Buenos Aires (1895) y Ciudad de México (1900). Hipnosis, magnetismo y el problema de lo paranormal en dos contextos latinoamericanos - Mauro Sebastián Vallejo (Centre de Recherches sur les Mondes Américains, 2015)
The main purpose of this paper is to develop a comparative study of the trips that the illusionist Onofroff made to the capital cities of Argentina and Mexico, in 1895 and 1900 respectively. During his successful trips through America, the illusionist stayed a long period of time in those two cities, and his presence caused different reactions from many participants of the cultural life. Physicians, spiritualists, writers and politicians coming from both contexts, felt attracted by the artist's shows of telepathy and hypnotism. In this article we try to show that the study of Onofroff's performances goes beyond the scope of the fin-de-siècle history of theater. By contrast, the analysis of his disturbing presence can work as a prism that perfectly reflects many areas of the cultural, scientific and ideological life of those cities. Through the description of several angles of the scientific cultures of the two cities, an explanation of the different responses aroused by Onofroff's shows will be outlined.